Complications Arising in the Oral Cavity after Polychemotherapy in Patients with Hemablastosis - Исламова Нилуфар Бустановна; Турдиев Жахонгир Авазбек угли (Scientific Trends, 2024)
Background: Today, it is believed that cancer does not appear immediately, but "is the last link in a long chain of changes that precede it, which can be to be called precancerous or precancerous." This postulate formulates the first law of malignant oncology: every cancer has its precancer, but not every precancer turns into cancer. Precancerous conditions, the presence of which is now generally recognized, are divided into obligate and facultative (Beck, 1933).